DIVERSITY OF THE MICROFITOPLANCTON IN THE OCEANIC WATERS AROUND CUBA - Loza-Álvarez, Sandra (2009)
The structure of the microphytoplankton community was evaluated in oceanic waters around Cuba during four cruises (February-March 1999, July-August 2003, March 2005 and August 2005). Samples were collected with 10 L Nasen bottles sub-surface level and were concentrated by inverse filtration through a 20 mm mesh-size net. The volume of filtered water per station ranged from 5-10 L. A total of 181 species of microalgae belonging to different taxonomic categories are reported. The microphytoplankton community, in terms of number of species, was dominated by diatoms (85) and dinoflagellates (47). Cianobacteria contributed 23 species and the dictiocophytes and primnesiophytes 23 species (mostly coccolithophorids). Among diatoms, the families Bacillariaceae, Chaetoceraceae and Rhizosoleniaceae contributed the greater number of species in the genera Nitzschia, Chaetoceros and Rhizosolenia.  In dinoflagellates, the families Ceratiaceae, Protoperidiniaceae, and Oxytosaceae, and the genera Ceratium, Protoperidinium, and Oxytoxum are emphasized. The oceanic waters north of Cuba presented a greater diversity of species (136) compared to those in the south (103) as demonstrated by a higher richness index (48.35) in the north versus the one found in the south (28.19).